Analytical solutions for a general mixed boundary value problem associated with motions of fluids with linear dependence of viscosity on the pressure - Vieru, Dumitru; Fetecau, Constantin; Bridges, C. (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady flow of incompressible Newtonian fluids with linear dependence of viscosity on the pressure between two infinite horizontal parallel plates is analytically studied. The fluid motion is induced by the upper plate that applies an arbitrary time-dependent shear stress to the fluid.
Keywords: analytical solutions; mixed boundary value problem; pressure-dependent viscosity